2013
DOI: 10.3802/jgo.2013.24.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin promotes epithelial ovarian cancer cell invasion by inducing epithelial-mesenchymal transition

Abstract: ObjectiveOver-expression of thrombin in ovarian cancer cells is associated with poor prognosis. In this study, we investigated the role of thrombin in inducing epithelial-mesenchymal transition (EMT) in SKOV3 epithelial ovarian cancer cells.MethodsAfter thrombin treatment SKOV3 cells were subjected to western blots, reverse-transcription PCR, and enzyme-linked immunosorbent assay to quantify EMT-related proteins, mRNA expression of SMAD2, DKK1, and sFRP1, and the secretion of matrix metalloproteinases (MMPs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 39 publications
1
21
0
1
Order By: Relevance
“…Characteristics of the mesenchymal phenotype include the expression of vimentin, α-SMA, fibronectin and N-cadherin. These EMT-related events were observed not only in CRC, but also in various types of human cancers [11,15], including esophageal cell carcinoma, and gastric, ovary and breast cancer [16,17,18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of the mesenchymal phenotype include the expression of vimentin, α-SMA, fibronectin and N-cadherin. These EMT-related events were observed not only in CRC, but also in various types of human cancers [11,15], including esophageal cell carcinoma, and gastric, ovary and breast cancer [16,17,18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that EMT in ovarian cancer is controlled by different cytokines and growth factors, such as mucin (MUC4) and CA125 (Ponnusamy et al 2010;Theriault et al 2011), bone morphogenetic protein 4 (BMP4), endothelin-1 (ET-1), epidermal growth factor (EGF), hepatocyte growth factor (HGF) and transforming growth factor-β (TGF-β) (Vergara et al 2010). More recently in an in vitro study, thrombin induced the expression of EMT proteins in EOC cells (Skov-3), which could be reversed with the use of inhibitors against thrombin (hirudin); this indicates that the use of anticoagulants might serve in the control of EOC progression (Zhong et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The manufacturer states that long-term animal studies to evaluate the carcinogenic potential of Floseal ® matrix have not been performed (13). In ovarian cancers -whose first-line treatment requires extensive surgery with high bleeding potential -thrombin has been shown to stimulate the growth of cancer cells in vitro (37). In our opinion, as long as the application of HM is restricted to the bleeding surface and all of the thrombin from HM is incorporated into the clot, the pro-cancerogenic action of HM will remain rather speculative.…”
Section: Discussionmentioning
confidence: 98%